Mechanically robust surface-degradable implant from fiber silk composites demonstrates regenerative potential - Wenhan Tian; Yuzeng Liu; Bo Han; Fengqi Cheng; Kang Yang; Weiyuan Hu; Dongdong Ye; Sujun Wu; Jiping Yang; Qi Chen; Yong Hai; Robert O. Ritchie; et al. (Bioactive Materials)
Through millions of years of evolution, bones have developed a complex and elegant hierarchical structure, utilizing tropocollagen and hydroxyapatite to attain an intricate balance between modulus, strength, and toughness. In this study, continuous fiber silk composites (CFSCs) of large size are prepared to mimic the hierarchical structure of natural bones, through the inheritance of the hierarchical structure of fiber silk and the integration with a polyester matrix. Due to the robust interface between the matrix and fiber silk, CFSCs show maintained stable long-term mechanical performance under wet conditions. During in vivo degradation, this material primarily undergoes host cell-mediated surface degradation, rather than bulk hydrolysis. We demonstrate significant capabilities of CFSCs in promoting vascularization and macrophage differentiation toward repair. A bone defect model further indicates the potential of CFSC for bone graft applications. Our belief is that the material family of CFSCs may promise a novel biomaterial strategy for yet to be achieved excellent regenerative implants.